Nogle Bemærkninger om Størrellen af Kornproduktionen. Foredrag, den 7de Febr. 1865. - Holst, L. (Tidsskrift for Landøkonomi, 2018)
Nogle Bemærkninger om Størrellen af Kornproduktionen. Foredrag, den 7de Febr. 1865.